Persepsi, Motivasi dan Pengetahuan perpajakan Terhadap Minat Mahasiswa Akuntansi Sebagai Konsultan Pajak - Yuliana Agas (Yayasan Literasi Ilmiah Indonesia, 2023)
This research aims to prove the influence of perception, motivation, and knowledge of taxation on the interest of accounting students in choosing a career as a tax consultant. This research uses a quantitative descriptive method and primary data using a questionnaire. This study took a sample of 85 active students of the accounting study program at the Tamansiswa University of Yogyakarta (UST). The data collection method is distributing questionnaires in the form of a Google form. The number of questionnaires processed was 85 questionnaires. Data analysis using multiple linear regression analysis. The results showed that perceptions, motivation and knowledge of taxation influenced the interest of accounting students in choosing a career as a tax consultant. Tax motivation and knowledge have a positive effect on the interest of accounting students in choosing a career as a tax consultant. Keywords: Perception, Motivation, Knowledge of Taxation, Accounting Student's Interest in a Career as Tax Consultant